Poised for Excellence Fundamental Principles of Effective Leadership in the Boardroom and Beyond - Mariama-Arthur, Karima (Springer International Publishing, 2018)
This book is an exceptional resource for leaders at every level across industries. An insightful guidebook comprised of 40 illuminating principles showcasing the fundamental competencies that impact performance in theboardroom and beyond, each chapter includes the following core components: 1) a robust, but succinct discussion introducing each principle; 2) key strategies providing straightforward guidance on how to master each principle; 3) a selection of thoughtful journal questions that allow for meaningful introspection, and finally, 4) a leadership challenge-a stretch goal-that brings each principle into immediate, scalable focus. Whether a seasoned or emerging leader, each reader will discover useful perspectives contained within each chapter designed to firmly orient their thinking and behavior towards leadership excellence. An enduring resource for circumstances in which every leader will inevitably find him or herself confronting, it will also serve as the "go to" professional development resource for elevating leadership brands and facilitating the necessary trench work required to develop competent and confident leaders regardless of industry or expertise. Different from traditional books that provide a one-dimensional view of what leadership is and do little more than categorize existing traits, Poised for Excellence breaks the mold. It creates the context for understanding leadership development as a holistic process: By focusing on the mastery of fundamental principles structured to develop the whole person through service to self and others, it ignites an evolutionary process that cultivates 360 degrees of effective leadership. It directs readers to stake a bold claim to their success and transform the way they show up in the boardroom and beyond.